2021
DOI: 10.3390/plants10122774
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Insights into the Role of Guard Cell Ion Channels in Abiotic Stress-Induced Stomatal Closure

Abstract: A stomatal pore is formed by a pair of specialized guard cells and serves as a major gateway for water transpiration and atmospheric CO2 influx for photosynthesis in plants. These pores must be tightly controlled, as inadequate CO2 intake and excessive water loss are devastating for plants. When the plants are exposed to extreme weather conditions such as high CO2 levels, O3, low air humidity, and drought, the turgor pressure of the guard cells exhibits an appropriate response against these stresses, which lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 224 publications
(302 reference statements)
0
11
0
2
Order By: Relevance
“…Generally, a single potassium ion channel is a homotetramer structure, consisting of four subunits symmetrically, and can only allow one potassium ion to pass through. 60,61 Shaker-type potassium ion channels can form heterotetramer structures, which is also an important characteristic of the Shaker channel. This structure allows plants to regulate the intracellular potassium transport activity in each organ or tissue relatively independently.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, a single potassium ion channel is a homotetramer structure, consisting of four subunits symmetrically, and can only allow one potassium ion to pass through. 60,61 Shaker-type potassium ion channels can form heterotetramer structures, which is also an important characteristic of the Shaker channel. This structure allows plants to regulate the intracellular potassium transport activity in each organ or tissue relatively independently.…”
Section: Discussionmentioning
confidence: 99%
“…Several ion channels, including the inward-rectifying K + channel KAT1, play a key role in the opening of stomata [ 140 , 141 ]. With KAT1 from A. thaliana , it was shown that this channel can interact with protein OST1 (open stomata 1) [ 142 ].…”
Section: Baker’s Yeast Saccharomyces Cerevisiae Fo...mentioning
confidence: 99%
“…Недавно выявлен ряд механизмов, которые участвуют в формировании устойчивости растений к осмотическому стрессу на уровне ионных каналов ПМ [123][124][125][126]. Показано, что анионный канал ZmSLAC1 (SLAC -slow anion channel) экспрессируется в ПМ устьичных клеток и обеспечивает закрывание устьиц при снижении водного потенциала среды [127].…”
Section: утечка электролитов из тканей растений при осмотическом стрессеunclassified
“…из устьичных клеток [123]. Кроме того, продемонстрировано, что повышенная экспрессия генов внутрьвыпрямляющих K + -каналов AKT1 (Arabidopsis K + transporter-1) и высокоаффинного K + -транспортера HAK1 (high affinity K + transporter-1) повышает устойчивость H. vulgare L. к засухе [124; 125].…”
Section: утечка электролитов из тканей растений при осмотическом стрессеunclassified